User Satisfaction Analysis of Primary Care Information Systems in Semarang City with EUCS Model - Prasetyowati, Asih; Kushartanti, Roro (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2018)
Abstract   Primary Care Information System (P-Care) is used at the first level health facility (FKTP) for the service of patients of the National Health Insurance. The purpose of this study was to determine the success of using the P-Care information system by evaluating the system using the End User Computing Satisfaction (EUCS) Model. This is a cross-sectional survey research with Primary Care information system objects. The variables studied were the user satisfaction factors of the p-care information system including content aspects, accuracy, format, ease of use, and timeliness. The research subjects were primary care information system operators with 61 FKTPs as samples. Data were analyzed using descriptive analytical methods. P-care application user satisfaction index was 75.5 (satisfied category). This shows that respondents generally have received the primary care information system. The lowest index on A1 (system accuracy), C1 (accuracy of information), and T1&2 (timeliness of information). The lowest average user satisfaction index is on aspects of system accuracy and timeliness. To improve the index of primary care information system user satisfaction, the BPJS needs to improve system monitoring, increase feedback and increase report output. FKTP can develop a bridging P-Care system and structuring the medical record system to be more effective and efficient.   Keywords : information systems, user satisfaction, primary care, EUCS Model     Abstrak   Sistem Informasi Primary Care (P-Care) digunakan pada fasilitas kesehatan tingkat pertama (FKTP) untuk pelayanan pasien Jaminan Kesehatan Nasional (JKN).  Kepuasan pengguna aplikasi P-Care merupakan faktor penting dalam kinerja sistem informasi. Tujuan penelitian ini adalah mengetahui keberhasilan penggunaan sistem informasi p-care dengan melakukan evaluasi sistem menggunakan End User Computing Satisfaction (EUCS) Model. Jenis penelitian adalah penelitian survey bersifat cross sectional dengan obyek sistem informasi Primary Care. Variabel yang diteliti adalah faktor kepuasan pengguna sistem informasi p-care meliputi aspek content, accuracy, format, ease of use, dan timeliness. Subyek penelitian adalah operator sistem informasi primay care dengan 61 sampel FKTP. Data dianalisis dengan cara diskriptif analitik. Indeks kepuasan pengguna aplikasi P-care adalah 75,5 (kategori puas). Hal ini menunjukkan bahwa responden secara umum sudah menerima sistem informasi primay care.  Indeks terendah pada A1 (akurasi sistem), C1 (ketepatan informasi), dan T1&2 (ketepatan waktu informasi). Rata-rata indeks kepuasan pengguna paling rendah pada aspek akurasi sistem dan ketepatan waktu. Untuk meningkatkan indeks kepuasan pengguna sistem informasi primary care, maka pihak BPJS perlu meningkatkan monitoring sistem, meningkatkan feedback dan penambahan output laporan. FKTP dapat mengembangkan sistem bridging p-care dan penataan sistem rekam medis untuk pelayanan pasien yang lebih efektif dan efisien.   Kata kunci : sistem informasi, kepuasan pengguna, primary care, EUCS Model